APLIKASI MESIN TEMPA MINI DI INDUSTRI PANDE BESI - Seno Darmanto; Didik Purwadi; Hartono Hartono; Mohd. Ridwan; Didik Ariwibowo; Alaya Fadllu Hadi Mukhamad (Sekolah Vokasi Universitas Diponegoro, 2020)
The PKUM scheme service activities for the Iron Pande Industry Group are carried out to improve the quality of production and export-based management. There are dozens of large, medium and small scale iron pande industries in Rejosari Pakis Magelang in Central Java and one of them is a member of the Mijil Karya group. The development of facilities for members of the iron pane industry is aimed at increasing the capacity / productivity and quality of iron pane products and carved bamboo furniture. And to achieve the capacity and quality of local content-based iron products and with local and national market share (exports), the service team prepares work steps or service activities including deepening company management management, especially in the flow of materials or goods and finance, deepening of improvements and improvements production units, deepening the improvement and refinement of local and national scale marketing (exports), completing showrooms to support marketing, implementation in partner industries and formulating indicators of success. Forging machine design of hammer system includes, overall machine design, component design, pully calculation, motor power calculation, belt calculation, shaft calculation, clutch calculation, peg calculation, welding strength calculation and flywheel analysis